2007
DOI: 10.1021/la063113q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Normal Pentane on the Surface of Rutile. Experimental Results and Simulations

Abstract: Adsorption isotherms and differential heats of normal pentane adsorption on microcrystalline rutile were measured at 303 K. The heat of adsorption of n-pentane on rutile at zero occupancy is 64 kJ/mol. The differential heats have three descending segments, corresponding to the adsorption of n-pentane on three types of surfaces. At low coverage (first segment), the adsorption is restricted to the rows A of the (110) faces along the 5-fold coordinatively unsaturated (cus) Ti(4+) ions with differential heat showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…in a previous work performed water, methanol and ammonia adsorption studies on the presently studied rutile (Rakhmatkariev 1987(Rakhmatkariev , 1988. As described in further detail elsewhere (Rakhmatkariev et al 2007), it was found that the density of the cus Ti 4+ ions on the most abundant face (110) corresponded to 72 µmol/g, whilst that on the other lower index faces -(100) and (101)corresponded to 26 µmol/g.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…in a previous work performed water, methanol and ammonia adsorption studies on the presently studied rutile (Rakhmatkariev 1987(Rakhmatkariev , 1988. As described in further detail elsewhere (Rakhmatkariev et al 2007), it was found that the density of the cus Ti 4+ ions on the most abundant face (110) corresponded to 72 µmol/g, whilst that on the other lower index faces -(100) and (101)corresponded to 26 µmol/g.…”
Section: Methodsmentioning
confidence: 61%
“…For instance, Mentzen et al (2007) have shown how calorimetric data can be exploited to complement crystal structure results and detect subtle sorbent-sorbate interactions on the molecular level which cannot be revealed by Rietveld-type powder diffraction profile structure refinements alone. We have shown in a previous work (Rakhmatkariev et al 2007) how adsorption microcalorimetry and Grand Canonical Monte Carlo computer simulations can complement some of the molecular insight which is provided by each technique. In that work, the adsorption of n-pentane on a rutile surface was studied using both the experimental adsorption calorimetric technique and Monte Carlo computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of comparison CH 4 adsorption enthalpy is also included here from our earlier work. 18 Enthalpy of adsorption on ZnDABCO for these hydrocarbons at zero occupancy is lower than that on other adsorbents like silicalite, 22 CuBTC, 26 microcrystalline rutile, 30 zeolites (MOR, MFI) 33 and MgDOBDC; 27 this indicates weaker host−guest interaction for ZnDABCO and will result in easier regeneration. Enthalpies of adsorption show a slight increase with loading due to an increase in lateral interactions between the adsorbate molecules.…”
Section: Resultsmentioning
confidence: 99%
“…27 However, saturation loading of C 2 H 6 and C 3 H 8 on both ZnDABCO and MgDOBDC would be similar due to their similar pore volumes. 27 The adsorption capacities for i-C 4 H 10 are higher than those in silica gel KC, 14 silicalite; 22 comparable to those in CuBTC, 20 activated carbon ASA-H. 29 The loading capacity for n-C 5 H 12 on ZnDABCO is significantly higher than that on BAX activated carbon, 15 microcrystalline rutile, 30 and silicalite. 31 Detailed comparison of adsorption capacities of ZnDABCO with that of other reported materials for all of the studied adsorbates is presented in Table 1.…”
Section: Methodsmentioning
confidence: 96%
“…Metal oxides, carbonaceous archetypes (nanotubes, nanohorns, etc. ), porous silicas, and metal-organic framework materials (MOFs), among other materials, currently represent significant components of nanomaterial research, because of their widespread use in optoelectronics, sensors, molecular adsorbents, fuel cells, separation chemistry, and catalysis. Understanding the nature of the interaction between adsorbed molecules and the surfaces of these materials is a necessity for developing synthetic methods to produce materials with specific functional (i.e., physical, chemical, and mechanical) properties.…”
Section: Introductionmentioning
confidence: 99%